Predictors of expectant fathers’ parental leave-taking intentions before birth: masculinity, fatherhood beliefs, and social support - Scheifele, Carolin; Van Laar, Colette; Steffens, Melanie C. (Frontiers in Psychology, 2024)
Despite continuing progress, men remain underrepresented in childcare, domestic labor, and other care work. Because parental leave is discussed as a gateway to increasing men’s childcare engagement, we aimed to gain insights into predictors of men’s parental leave-taking intentions during the transition to parenthood. Using outcomes on a continuum from behavioral preferences to more behavior-oriented measures, we examine how masculinity and fatherhood beliefs as well as social support become relevant during men’s formation of their leave-taking intentions. Planned analyses of data collected from 143 expectant fathers in Belgium and Germany revealed that the support men perceive from their partners for taking leave predicts their parental leave-taking desire, intention, and planned length of leave. Moreover, men’s conception of a prototypical man, especially in terms of agency, was linked to their desire to take leave. Against expectations, father role attitudes and workplace support did not emerge as relevant predictors of men’s intended leave-taking. Results of exploratory analyses suggest that care engagement of peers, expected backlash, and self-efficacy beliefs additionally play a role in men’s intended leave-taking. We discuss parental leave as a negotiation process within couples and review the role of men’s normative environment for their intended leave-taking.